The path to the construction of a domestic and international dual cycle of China’s shipping industry - Cao, Xingguo; Zhang, Xu; Chang, Yen-Chiang (Frontiers in Marine Science, 2023)
The shipping industry is the forerunner of a new domestic and international dual-cycle development pattern in the People’s Republic of China (hereinafter referred to as ‘PRC’). The PRC has formed an array of policy innovations and legal instruments to provide impetus for the dual-cycle development of the shipping industry by the construction of the Pilot Free Trade Zones/Free Trade Port internally and the signing of high-level Free Trade Agreements internationally, whereas the former focus on development opportunities for the shipping industry in terms of opening up the shipping market, shipping facilitation, shipping tax burden reduction, and shipping digitization, while the later bring benefits in terms of increasing the total volume of shipping cargo and promoting the efficiency of international shipping circulation. The path to the construction of a domestic and international dual-cycle of the shipping industry in the future still entails the deep digging of policy innovations and legal instruments to promote a deeper internal reform and international cooperation in shipping. It is also deemed necessary to optimize shipping related services, improve deployment of shipping resources, and strengthen the innovation of new development model with combination of new technologies.